THE STUDY OF SOLUTION ABSORPTION AND DIFFUSION COEFFICIENT IN EPOXY COMPOSITE REINFORCED WITH GLASS FIBERS - Sheelan R. Areef (Engineering and Technology Journal, 2008)
Diffusivity behavior and diffusion coefficient was investigated in this paper for epoxy compositereinforced with glass fibers (woven roven and random direction) together as a sandwich with volumefraction (44). The samples were immersed in different solution for equal time at constant temperature(room temperature ±18oC). The result show that the relative mass gain increased with increasing theimmersion time till they tend saturation moisture mass (M∞) after that the relative mass gain decreased.The result show that the samples immersed in (kerosene) solution had higher mass gain while thesamples immersed in distill water had lower mass gain and the samples immersed in other solution(Benzene, HNO3, KOH, H2O as received) had relatively mass gain between them.Also the results show that the samples immersed in benzene has maximum diffusion coefficient(30.219mm2/day) which means minimum absorption resistance while the samples immersed in (H2O asreceived) has minimum diffusion coefficient (0.191mm2/day) (maximum absorption resistance).